حدیث کی تشریعی حیثیت میں امام طحاوی کا اسلوب: The style of Imam Tahawi in the legislative status of hadith - Dr. Hafiz Farhan Arshad (DIRAYAT, 2025)
The Quran and Hadith are intricately connected. The Quran is the book of Allah, and Muhammad ﷺ serves as its first commentator. This role as the primary interpreter of the Quran is unique to the Messenger of Allah, ﷺ, and no one from the Ummah shares this distinction. Muhammad's ﷺ interpretation of the Holy Quran is definitive, and every Muslim must adhere to it. The teachings of the Quran regarding religion and Shariah are fundamentally principled. Consequently, Rasulullah ﷺ holds the greatest authority in interpreting the Quran, and no interpretation other than his is considered valid. Therefore, after the Book of Allah, it is essential to refer to Hadith and Sunnah. No one has the authority to interpret the Quran more than the Prophet, and no interpretation can be accepted that contradicts his. Imam Tahawi has beautifully illustrated the interpretive significance of Sunnah with various examples.